2011
DOI: 10.1590/s0066-782x2011005000112
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do desfecho entre a cardiopatia chagásica e a miocardiopatia dilatada idiopática

Abstract: Background: Little is known about the outcome of patients with Chagas cardiomyopathy in comparison to that of patients with Idiopathic Dilated Cardiomyopathy in the contemporary era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“…It has been observed that the occurrence of myocarditis is correlated with clinical severity, ASY patients having minimal inflammation, while patients with advanced CCC display frequent and intense myocarditis [5]. Approximately 1/3 of patients developing CCC present a particularly lethal form of dilated cardiomyopathy, with shorter survival than idiopathic dilated cardiomyopathy [6]. In addition, CCC is associated with a worse prognosis and survival than other cardiomyopathies of non-inflammatory etiology (NIC) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the occurrence of myocarditis is correlated with clinical severity, ASY patients having minimal inflammation, while patients with advanced CCC display frequent and intense myocarditis [5]. Approximately 1/3 of patients developing CCC present a particularly lethal form of dilated cardiomyopathy, with shorter survival than idiopathic dilated cardiomyopathy [6]. In addition, CCC is associated with a worse prognosis and survival than other cardiomyopathies of non-inflammatory etiology (NIC) [7].…”
Section: Introductionmentioning
confidence: 99%
“…20,000 deaths attributable to Chagas disease occur annually, typically due to CCC [3]. Heart failure due to CCC has a worse prognosis with 50% shorter survival when compared to other cardiomyopathies of different etiologies [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…RBBB and left anterior fascicular block are found in about 40 % of patients with Chagas heart failure, which is higher than that seen in CHF due to other types of cardiomyopathy. 17,18,21 The association between RBBB and left anterior fascicular block, which is more frequent in patients with Chagas cardiomyopathy, 22 should alert physicians to the possibility of Chagas heart failure. In contrast, the prevalence of left bundle branch block (LBBB), which is frequently found in patients with non-Chagas cardiomyopathy, 23 is lower in Chagas heart failure.…”
Section: Peculiarities Of Subsidiary Testsmentioning
confidence: 99%